A Quantum Encryption Algorithm based on the Rail Fence Mechanism to Provide Data Integrity - Ali, Arshad; Farquad, M. A. H.; Atheeq, C.; Altaf, C. (Engineering, Technology & Applied Science Research, 2024)
The rapid development of quantum computer technology poses an increasing threat to conventional encryption algorithms, and accordingly, more advanced security practices need to be developed. The current paper presents an innovative quantum cryptographic mechanism that combines classical encryption techniques with quantum principles such as superposition, entanglement, and uncertainty to enhance data security in digital communication. The proposed scheme, defined as Enhanced Quantum Key Distribution (EQKD), demonstrates superior performance in key metrics, including Quantum Bit Error Rate (QBER), fidelity, key distribution rate, and resilience to eavesdropping. In particular, EQKD achieves lower QBER and higher fidelity over longer distances while also enhancing key generation efficiency and increasing the probability of detecting eavesdropping attempt. These findings highlight the effectiveness of EQKD in improving the security and reliability of quantum cryptographic systems.